Proclaiming a prophecy empty of substance? A pragmatist reconsideration of global governance. (October 2022) - Franke, Ulrich; Hofferberth, Matthias
In 1995, the UN Commission on Global Governance published their "Our Global Neighbourhood" report and the academic journal "Global Governance: A Review of Multilateralism and International Organizations" was launched. Both events in retrospect play a significant role in the emergence of global governance thinking and practice in world politics. Despite inherent ambiguities, this idea since then gained massive traction and became both a modality and a heuristic of world politics. Advancing a pragmatist framework, we unpack global governance in terms of the beliefs which underline and guide it. These beliefs are important since they, as rules for action, define the scope of global governance as a theoretical and a political concept. Reconstructing these beliefs directly from the 1995 report, the article highlights the inherent conflations of normative and analytical commitments indicative of global governance. As a projection surface of all kinds, we believe such a reconsideration of global governance is important to (a) reveal the baselines of its thinking and practice, (b) indicate how its normative and analytical ambitions overlap and conflate, and (c) contribute to a more reflective discussion on the idea which explicitly considers its inherent normativity. At the same time, we hope to show the value of a pragmatist framework on beliefs for the study of world politics.